Advanced Magnetic Resonance Imaging Techniques in Assessment of Pediatric Patients With Epilepsy - Elshenawy, Esraa Ahmed; Badawy, Manal Ezzat; Elgammal, Tarek Mohamed; Ghieda, Usama Elsaeid; AboKhadrah, Rania Sobhy (Journal of Neonatal Surgery, 2025)
Background: Epilepsy is a neurological condition that is prevalent among individuals of all ages, races, social classes, and geographical locations. This research aimed to assess the value of arterial spin labeling (ASL), diffusion tensor imaging (DTI), and magnetic resonance spectroscopy (MRS) as novel MRI approaches, in detecting the epileptogenic zone in pediatric patients with epilepsy of unknown cause who had normal conventional magnetic resonance imaging. Methods: This prospective case-control research involved 60 patients aged from two to 18 years, both sexes, with intractable epilepsy with unknown cause while conventional magnetic resonance imaging was normal and 60 healthy volunteers of nearly similar ages as control group. All patients were subjected to MRS, DTI and ASL perfusion. Results: Both the epilepsy and control groups showed significant differences in hippocampal fractional anisotropy, mean diffusivity (MD), ASL, NAA/CHO+Cr, or NAA/CR (P<0.001). The hippocampus's fractional anisotropy (FA) and MD showed extremely strong agreement with NAA/Cr and NAA/Cho + Cr, ASL showed good agreement with both of these parameters, while MRS and ASL parameters showed poor agreement with DTI parameters. There was poor agreement between MRS, DTI and ASL with electroencephalography finding. Conclusions: By combining MRS, DTI, and ASL, diagnostic accuracy is significantly increased compared to using each sequence individually. This combination also yields great results in localizing and lateralizing of the epileptogenic focus.